Suppression of cancer growth by non-viral gene therapy based on a novel reactive oxygen species-responsive promoter - Policastro, Lucia Laura (2009)
Increased reactive oxygen species (ROS) production has been reported as a distinctive feature of different pathologies including cancer. Therefore, we assessed whether increased ROS production in the cancer microenvironment could be selectively exploited to develop a selective anti-cancer therapy. For this purpose we constructed a novel chimeric promoter, based on a ROS-response motif located in the VEGF gene promoter placed, in turn, downstream of a second ROS-response motif obtained from the early growth response 1 (Egr-1) gene promoter. The activity of the chimeric promoter was largely dependent on variations in intracellular ROS levels and showed a high inducible response to exogenous H2O2. Transient expression of the thymidine kinase gene (TK) driven by the chimeric promoter, followed by gancyclovir administration, inhibited human colorectal cancer and melanoma cell growth in vitro and in vivo. Moreover, electrotransfer of the TK gene followed by gancyclovir (GCV) administration exerted a potent therapeutic effect on established tumors. This response was improved when combined with chemotherapeutic drugs. Thus, we show for the first time that a distinctive pro-oxidant state can be used to develop new selective gene therapeutics for cancer.